(untitled) (Journal of Naval Architecture and Marine Engineering, 2017)
The effects of an overlapping stenosis on blood flow characteristics in an artery have been studied. Blood has been represented by a couple stress fluid. The flow equations have been linearised and the expressions for pressure drop, resistance to the flow and wall shear stress have been derived. The results are shown graphically. It is observed that the resistance to the flow, pressure drop and wall shear stress increases with height and length of the stenosis. And it is noticed that the resistance to the flow and pressure drop decreases with couple stress fluid parameters. But wall shear stress increases with couple stress fluid parameters.